My whirlwind journey to understanding and loving groupwork - Ginzburg, Anna (Groupwork, 2017)
Abstract: This essay covers a three day conference held by the International Association for Social Work with Groups (IASWG) Group Work Camp on Lake Geneva. The essay describes the activities, schedule and emotional state of the participants. The author, as one of the participants, displays her emotions and thoughts about the process and supports it with theoretical inserts about group work process and stages. Keywords: groups; therapy; group therapy; social work; stages; mutual; motivation; exploration; play; self consciousness; transformation; camp; evidence; groupwork